Design and implementation of integrated security and safety system based on internet of things - Khalaf Mohammed, Omar; Bayat, Oguz; M. Marhoon, Hamzah (International Journal of Engineering and Technology, 2019)
In the recent years, with the development of technology, it has been noticed that thefts are increasing for various public and private establishments, homes, offices, companies, etc., as well as increased fires due to sabotage, for example, or because of the gas leak inside the house. The homes when their owners are abroad for vacation or business trip the danger increased so, it is necessary to find means and systems for the security and safety, in this paper the implemented system based on two parts, the first part is responsible on the security and the second part responsible on the safety. The implemented system based on the Arduino NANO microcontroller, gas sensor, flame sensor, PIR sensor, laser and LDR, the gas sensor used in order to detect the gas leak, the flame sensor used to detect the fire, the PIR sensor and the LDR used to detect the motion. In this work the security made up from two level of security where, the first level based on PIR sensor to detect the motion and second level based on the laser and LDR when the thief tries to cutting the laser beam or passing from the front of PIR sensor the alarming system will be turning on and send SMS message to alert the home owner in the same time the another message will be appears on the specific GUI programmed by HTML language this done by the NodeMCU module where this module allows the home owner from accessing to his system wirelessly in other words supports the IoT technology , additionally through this GUI user can turning ON/OFF the outdoor lighting system and monitor his home in case gas leak, fire and in the case of a thief attempting to enter the house.
Keywords: Arduino NANO; Gas sensor; Flame sensor; LDR; PIR; NodeMCU; IoT.